The art of cyberwarfare an investigator's guide to espionage, ransomware, and organized cybercrime - DiMaggio, Jon (No Starch Press Inc., 2022)
This book is a guide to understanding the players in today's cyber wars, the techniques they use, and the process of analyzing their attacks. It provides an overview of actual cyber attacks conducted by nation-state actors and other advanced organizations and informs how defenders can track and attribute future attacks"-- Provided by publisher.